Declaración de las canciones oscuras of Luis Felipe Fabre, A Palimpsestuous Approach to San Juan De La Cruz (Palimpsesto, 2022)
Declaración de las canciones oscuras (2019) is a parody written by Mexican writer Luis Felipe Fabre (1974). Through a series of palimpsests, the author portrays legends, myths, chronicles, worries, true and fictitious situations about the historical transportation of Fray Juan e la Cruz’s body from his native town Ubeda to Segovia. The novel is nuanced with the reflection of verses, Dark Night (of the Soul), Spiritual Chant and Love Flame from the reforming author. The enigmas from those poems are deciphered in an antithetical way: straight forward and burlesque in order to illustrate the occurrences during the secret journey of the poet’s body. Through the use of a supposed traditional and baroque language, the narrator conceives a story with traces of raw humor from a picaresque literature, the inescapable nonsense of the theater of the absurd and the cervantine heritage in sayings, characters, and situations during the generic crossing between poetry, drama and prose.
Keywords: Fabre; San Juan de la Cruz; Castillo; Parody; Palimpsest